Original creations with papier mcachbe. - Anderson, Mildred (Sterling crafts books, 1968)
Briefly explains the technique of using papier mcachbe and gives directions for making many useful and decorative objects, such as a bead curtain, lamp shades, dishes, and a puppet theater.